2015
DOI: 10.1177/1076029615614396
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Venous Thromboembolism in Surgical Patients Using a Mandatory Risk-Scoring System: 5-Year Follow-Up of an American College of Surgeons National Surgical Quality Improvement Program

Abstract: A compulsory risk assessment for VTE has led to an overall improvement in DVT/PE rates in the surgery institute and for GV surgery to become an exemplary site for the ACS NSQIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…However, as many of the components in the Caprini RAM pertain to individual risk factors rather than operation-specific risk factors, some clinicians still prefer to use this RAM as a reminder of common individual VTE risk factors to aid in their VTE risk assessment for these populations RAMs have been implemented successfully and result in higher compliance with guideline-directed prophylaxis strategies. 40 The performance of existing RAMs has not been compared directly. Thus, the 2005 Caprini and 2007 Rogers scores are currently endorsed in AT9.…”
Section: Thrombosis Risk Assessmentmentioning
confidence: 99%
“…However, as many of the components in the Caprini RAM pertain to individual risk factors rather than operation-specific risk factors, some clinicians still prefer to use this RAM as a reminder of common individual VTE risk factors to aid in their VTE risk assessment for these populations RAMs have been implemented successfully and result in higher compliance with guideline-directed prophylaxis strategies. 40 The performance of existing RAMs has not been compared directly. Thus, the 2005 Caprini and 2007 Rogers scores are currently endorsed in AT9.…”
Section: Thrombosis Risk Assessmentmentioning
confidence: 99%
“…8,32 A quality improvement initiative at Sheikh Kalifa Medical City managed an increase to 100% compliance with pharmacoprophylaxis ordering and a significant decrease in their observed/expected ratio for VTE after implementation of a hard stop for performance of VTE risk assessment. 7 Changing provider's practice patterns is possible through a structured effort at either the division or department level. A "champion" approach that incorporates structured education sessions and monthly reminders has been shown to significantly increase appropriate risk stratification and compliance with provision of chemoprophylaxis.…”
Section: Quality Improvement Initiativesmentioning
confidence: 99%
“…Hachey et al investigated the effectiveness of risk stratification with the Caprini RAM in a cohort of thoracic surgery patients. 25 The authors' institution (Boston University) uses the Caprini RAM for all surgical patients preoperatively, and categorizes patients similarly to other institutions, with low risk (0-4), moderate risk (5)(6)(7)(8), and high risk (9). Of 126 patients analyzed, 19.2% fell in the high-risk, 48% in the moderate-risk, and 32.8% in the low-risk category, and overall VTE rate was 2.3%.…”
Section: Cardiac and Thoracic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that ACS NSQIP-driven quality improvement projects decrease surgical complications, lower costs, and lead to better quality of surgical care [5,6]. Similarly, we have been able to reduce surgical complications using several ACS NSQIP-driven quality improvement projects [7][8][9][10]. We aim to evaluate our complication rates over time and the financial impact of joining and maintaining ACS NSQIP to SKMC's bottom line by evaluating our cost savings.…”
Section: Introductionmentioning
confidence: 99%